Gendered spaces in Bobbie Ann Mason's In Country - McDermott, Sinead (Revista Leitura, 2019)
This essay focuses on Bobbie Ann Mason's 1985 novel, In Country, in order to explore some aspects of the relationship between gender and space. It argues that spaces are integral to the novel's plot and its representation of female subjectivity. Gender plays a part in how the novel's protagonists experience and occupy space, and spaces are also produced as gendered through representation. Focussing on public and private spaces, the road, and the Vietnam Veterans Memorial, the essay argues that such spaces are shaped by society's assumptions about gender, but they also serve to produce gendered subjectivities. DOI: 10.28998/0103-6858.2008v1n41p121-147